PENDIDIKAN KEWIRAUSAHAAN BAGI WARGA GEREJA DI ERA DIGITAL - Talizaro Tafonao (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
In this study, the author studied education for church members: the role of the church in building and empowering the economy of the church member in the digital era. This study departs from the writer's observation empirically, where the church today only focuses on the spiritual side without thinking about the church member's life. The author emphasized in this paper that the church is not only present as preachers and prayer for the church members, but the church must provide a solution to the problems faced by the church members. The method used in this study is the qualitative research method. The author examines the church's role in building and empowering the economy of the church members in the digital era. The author's analysis process uses various reliable sources and electronic resources to support the writer's analysis. The results show that by utilizing technology as a business opportunity, the church could reducing the unemployment and poverty of the church members. The purpose of this study is to encourage every church to have a qualified innovation in answering the challenges in the digital era as an opportunity to create employment for church members.